Pengaruh Promosi, Citra Merek, dan E-Service Quality terhadap Keputusan Pembelian: Studi pada Pengguna Platform Shopee di Jakarta Selatan - Abdullah Khalil Mukhtar; Agus Sriyanto (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
This study aims to determine whether promotion influence purchase decisions, brand image influence purchase decisions, e-service quality influence purchase decisions. This research includes quantitative research. The research sample used incidental sampling with a total of 99 respondents. Data were analyzed with SPSS 30. The result of this study were that promotion had an effect on purchase decisions, brand image had an effect on purchase decisions, e-service quality not had an effect on purchase decisions.